Endogenous Institution Formation under a Catching-up Strategy in Developing Countries - Lin, Justin Yifu (Washington, DC: World Bank, 2012)
This paper explores endogenous institution formation under a catching-up strategy in developing countries. Since the catching-up strategy is normally against the compartive advantages of the developing countries, it can not be implemented through laissez-faire market mechanisms, and a government needs to establish nonmarket institutions to implement the strategy. In a simple two-sector model, the authors show that an institutional complex of price distortion, output control, and a directive allocation system is sufficient to implement the best allocation for the catching-up strategy. Furthermore, removing any of the three components will make it no longer implementable. The analysis also compares the best allocation and prices under the catching-up strategy with their counterparts under no distortions. The results of this paper provide important implications for understanding the institution formation in the developing countries that were pursuing a catching-up strategy after World War II.